2019
DOI: 10.1016/j.solener.2019.02.062
|View full text |Cite
|
Sign up to set email alerts
|

Renaturing a microclimate: The impact of greening a neighbourhood on indoor thermal comfort during a heatwave in Manchester, UK

Abstract: Ti t l e R e n a t u ri n g a mi c r o cli m a t e : t h e i m p a c t of g r e e ni n g a n ei g h b o u r h o o d o n in d o o r t h e r m al c o mfo r t d u ri n g a h e a t w a v e in M a n c h e s t er, UK

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…The simulations were run for 26 hours, starting from midnight[36]. Maximum UHI measured in Manchester was 2.3 ᵒC in 2018[37].…”
mentioning
confidence: 99%
“…The simulations were run for 26 hours, starting from midnight[36]. Maximum UHI measured in Manchester was 2.3 ᵒC in 2018[37].…”
mentioning
confidence: 99%
“…GIS-based methodology to evaluate green roofs and green urban areas 9 [4][5][6][7][8][9][10][11][12] Outdoor thermal comfort: UHI mitigation strategies and thermal comfort indexes 20 [2,4,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Energy savings and Indoor thermal comfort from Green roofs 5 [1,[31][32][33][34] 2.…”
Section: No Of Papers Sourcementioning
confidence: 99%
“…It was found that, in Manchester, during the hottest day of 2017, by adding 17% more trees, indoor thermal comfort was improved by 20.8%. The regeneration of cities could be a solution for future warmer climates [32].…”
Section: Energy Savings and The Indoor Thermal Comfort Of Green Roofsmentioning
confidence: 99%
“…As this figure shows, traditional buildings in hotter climates were built and covered with high albedo materials like plaster. While the UHI in Manchester was 2.3 • C in summer 2018 (meaning that the city centre of Manchester was 2.3 • C hotter than its surrounding) [32], Akbari et al [33] showed that Santorini is cooler than its surroundings.…”
Section: Urban Surface Materials and Natural Elementsmentioning
confidence: 99%